CLIMATE CHANGE MITIGATION HADIṠ PERSPECTIVE: Thematic-Correlative Approach - Azhari, Ainul (RIWAYAH, 2024)
Climate change is a critical issue threatening life on earth, requiring active human efforts and support from religion to address it. This study analyzes the moral messages in hadiṡ related to climate change mitigation through a thematic-correlative approach. This research uses qualitative methods, library research, and takhrij al-hadis, data were examined using content analysis, al-jarh wa al-ta’dil, and tawarikh al-ruwat, along with internal and external hadīṡ criticism. The findings confirm that three hadīṡs addressing climate change mitigation are of high quality, making them valid references for Islamic teachings (maqbūl al-hujjah) and applicable in practice. Thematically, these hadīṡ align with efforts to combat climate change, emphasizing the importance of preserving water resources and preventing ecosystem damage. Islam highlights water conservation and responsible usage, recognizing water as vital for all living beings. Mitigation efforts include reforestation, rehabilitating degraded lands, and prohibiting the felling of wild trees to sustain ecosystems. These teachings affirm Islam’s proactive approach to environmental preservation through hadis, advocating for sustainable practices that align with the broader goal of mitigating climate change impacts. [Perubahan iklim adalam masalah krusial yang mengancam kehidupan di bumi, membutuhkan upaya aktif manusia dan dukungan agama untuk mengatasinya. Penelitian ini menganalisis pesan moral dalam hadis yang berkaitan dengan mitigasi perubahan iklim melalui pendekatan tematik-korelatif. Penelitian ini menggunakan metode kualitatif, penelitian kepustakaan, dan takhrij al-hadits. Teknik analisis data menggunakan analisis isi, al-jarh wa al-ta’dil, dan tawarikh al-ruwat, serta kritik hadis dari aspek internal dan eksternal. Hasil penelitian ini menunjukkan bahwa tiga hadis yang membahas mitigasi perubahan iklim memiliki kualitas tinggi, sehingga dapat dijadikan referensi yang sah dalam ajaran Islam (maqbūl al-hujjah) dan diterapkan dalam praktik. Secara tematik, hadis-hadis ini sejalan dengan upaya mengatasi perubahan iklim, menekankan pentingnya menjaga sumber daya air dan mencegah kerusakan ekosistem. Islam menekankan konservasi air dan penggunaannya secara bijak, mengingat air adalah kebutuhan esensial bagi semua makhluk hidup. Upaya mitigasi meliputi reboisasi, rehabilitasi lahan yang terdegradasi, dan larangan penebangan pohon liar untuk menjaga keberlanjutan ekosistem. Ajaran ini menegaskan pendekatan proaktif Islam melalui hadis terhadap pelestarian lingkungan, mendorong praktik berkelanjutan yang sejalan dengan tujuan mitigasi dampak perubahan Iklim.]